Down to Earth : Agriculture and Poverty Reduction in Africa - Christiaensen, Luc; Demery, Lionel (Washington, DC : World Bank, 2012)
This book contributes to the debate about the role of agriculture in poverty reduction by addressing three sets of questions: Does investing in agriculture enhance/harm overall economic growth, and if so, under what conditions? Do poor people tend to participate more/less in growth in agriculture than in growth in other sectors, and if so, when? If a focus on agriculture would tend to yield larger participation by the poor, but slower overall growth, which strategy would tend to have the largest payoff in terms of poverty reduction, and under which conditions?